Growth and Survival Rate of Gurami Fish (Osphorenemus gouramy) by Giving Different Doses of Bromelin Enzymes in the Fish Meal on Aquaponics Resirculation System - Adri Firmansyah; Niken Ayu Pamukas; Mulyadi Mulyadi (Jurusan Budidaya Perairan, Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This study aims to determine the best doses of bromelin enzyme in commercial feed to increase the growth and survival rate of gouramy seeds in the aquaponic recirculation system. The research was carried out in February 20 to April 30, 2019 at the Fish Hatchery Unit, Faculty of Fisheries and Marine, Riau University. The fish were kept in a bucket with volume of 40 L water and stocking density of 20 ind/40 L. L using experimental method of completely randomized design (RAL), one factor with three treatments and three replications. The treatments were P0 = without the addition of bromelain enzymes, P1 = addition of bromelain enzymes 1.5% /kg of feed, P2 = addition of bromelain enzymes 2.25% /kg of feed and, P3 = Addition of bromelin enzymes 3% /kg of feed. The results showed that the administration of bromelin enzymes with different doses in the feed in aquaponic recirculation system culture showed an influence on weight growth, absolute length, specific growth rate, feed efficiency, feed conversion ratio and survival of gouramy. The best treatment was obtained in P3, namely administration of bromelain enzymes at a dose of 3% / kg of feed with an absolute growth weight value of 20.43g, absolute growth length 2.50 cm, specific growth rate 1.08%, feed conversion 1.16 and fish survival rate 88.3. %. The quality of water during the study were temperature 27-28.6 0C, pH 6.5-7.3, dissolved oxygen 4.8-6.3 ppm and ammonia 0.02-0.08 mg / L